Dog soldiers - Marshall, Neil; Figg, Chrisopher; Reeve, Tom; Allen, David E. (Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils.), 2002)
Something evil lurks in the wilds of Scotland, and this unfortunate troop of soldiers are about to stumble upon it. A routine exercise takes an unexpected turn when the troop discovers a ravaged bunch of dead soldiers out in the woods. With dusk quickly turning to night, and an ominous full moon lighting up the sky, the soldiers decide to hide-out in an abandoned farmhouse. With their supplies and morale both in short supply, the soldiers become trapped in the farmhouse by a pack of hungry werewolves who seem hellbent on enjoying the soldiers for dinner. Can anything stop them?